Solve for x x

Algebra Level 2

Solve for x x in the following expression

x = 6 + 6 + 6 + x= \sqrt{6+\sqrt{6+\sqrt{6+\sqrt{\dots}}}}

1 2.5 2 Can not be solved 3 6

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

Hana Wehbi
Jul 6, 2017

The expression can be written as x = 6 + x x 2 x 6 = 0 x=\sqrt{6+x}\implies x^2-x-6=0 by squaring both sides.

( x 3 ) ( x + 2 ) = 0 x = 3 (x-3)(x+2)=0 \implies x=3 , the other root is negative so we reject it.

How do we know the limit defining this infinitely nested function converges?

Zach Abueg - 3 years, 11 months ago

Log in to reply

If you look at it like this 6 1 / 2 + 6 1 / 4 + 6 1 / 8 + + 6 1 / 2 n 6^{1/2}+6^{1/4}+6^{1/8}+\dots+ 6^{1/2n} isn't that a geometric series whose ratio is less than one which indicates it converges.

Hana Wehbi - 3 years, 11 months ago

x = 6 + 6 + 6 + . . . x 2 = 6 + 6 + 6 + + . . . x 2 = 6 + x x 2 x 6 = 0 ( x 3 ) ( x + 2 ) = 0 x 1 = 3 x 2 = 2 x=\sqrt { 6+\sqrt { 6+\sqrt { 6+... } } } \\ { x }^{ 2 }=6+\sqrt { 6+\sqrt { 6+\sqrt { +... } } } \\ { x }^{ 2 }=6+x\\ { x }^{ 2 }-x-6=0\\ (x-3)(x+2)=0\\ \Leftrightarrow { x }_{ 1 }=3\\ \Leftrightarrow { x }_{ 2 }=-2

Thus, the value of x x that satisfies is x = 3 x = 3 .

Thank you for sharing your solution.

Hana Wehbi - 3 years, 11 months ago

I think there is a typo when writing x 2 x_2 .

Hana Wehbi - 3 years, 11 months ago

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...